Clinical analysis of pulmonary mucosa-associated lymphoid tissue lymphoma coexisting with lung cancer - Heng Yang; Man-Hui Li; Qiu-Hong Li; Ke-Bin Cheng; Wei-Jun Cao (BMC Cancer)
Abstract Background Primary pulmonary Mucosa-associated lymphoid tissue (MALT) lymphoma is a sporadic disease with a favorable prognosis. Particularly, pulmonary MALT lymphoma coexisting with lung cancer is not only rare but also prone to misdiagnosis. The clinical characteristics and prognostic factors of this co-occurrence, however, remain poorly understood. Methods We retrospectively analyzed the clinical, imaging, genetic mutations and pathological data among adult patients with pulmonary MALT lymphoma coexisting with lung cancer who were confirmed by pathological examinations after operation at Shanghai Pulmonary Hospital between 1st January 2013 and 31st May 2024. Results After exclusions, a total of 14 patients were included in the study, of which eleven patients were women and only 3 were men, with a median age of 57 [IQR: 53–67] years. Pulmonary MALT lymphoma presented a median diameter of 14 mm (IQR: 6–23). Nodule was the most frequent CT feature and existing pattern of pulmonary lesions (n = 8). The lung cancer was with a median diameter of 10.7 [IQR:6,20] mm, with nodules as the predominant CT feature (n = 12). Six patients manifested dual primary malignancies within the same lung lobe, termed collision tumors, whereas the remaining eight had lesions in different lobes. Five cases exhibited EGFR mutant, and one case showed no mutation. 13 patients were pathological confirmed with lung adenocarcinoma and one with microcarcinoma. Postoperatively, all-cause mortality rate was low, indicating a positive prognosis. One patient died 41 months after surgery due to a pulmonary infection, while the remaining 13 patients were in good condition with an average follow-up of 37.92 months. Conclusions In patients with pulmonary lesions, particularly multiple lesions, comprehensive preoperative evaluation is crucial to prevent misdiagnosis or missed diagnoses. Besides, surgical resection is desirable when both lung cancer and MALT are at an early stage and can be resected with minimally invasive surgery (minimally lung resection).